Dinamika Pelaksanaan Hukum Adat Dayak Ngaju dalam Penyelesaian Sengketa Tanah di Kalimantan Tengah - Dede Suryanto, Dede Suryanto (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research discusses land dispute resolution in Central Kalimantan with a focus on the implementation of Dayak Ngaju Customary Law. The Dayak community has a strong tradition of customary law that plays a crucial role in governing their lives. Although there is an option to use the court system for dispute resolution, some parties choose customary law as they believe it is more effective and suitable for land-related issues. However, the recognition of Dayak customary law by the government poses challenges to its implementation. While local governments acknowledge and protect Dayak Ngaju customary law, there are still shortcomings in the legal certainty that supports this customary law. In land dispute resolution, customary institutions such as Damang Kepala Adat play a significant role in regulating and resolving conflicts based on customary law principles. The mechanisms for resolving land disputes through Dayak Ngaju customary law involve customary deliberation and mediation. There are also rules and sanctions that govern the implementation of customary law. This research provides a better understanding of the benefits of customary institutions in land dispute resolution. The research methodology employed is empirical legal research with a socio-legal approach. Data were obtained through in-depth interviews and participatory observation. In the resolution of land disputes using Dayak Ngaju customary law, there are obstacles such as the influence of modernization and the lack of government attention. The dynamics of implementing Dayak Ngaju customary law have a significant impact on land dispute resolution, emphasizing the importance of customary law and respect for customary values. To enhance the effectiveness of customary law implementation, efforts are needed to raise awareness and gain broader recognition of customary law by the government.